2021
DOI: 10.3390/pathogens10111514
|View full text |Cite
|
Sign up to set email alerts
|

Highly Specific Sigma Receptor Ligands Exhibit Anti-Viral Properties in SARS-CoV-2 Infected Cells

Abstract: (1) Background: There is a strong need for prevention and treatment strategies for COVID-19 that are not impacted by SARS-CoV-2 mutations emerging in variants of concern. After virus infection, host ER resident sigma receptors form direct interactions with non-structural SARS-CoV-2 proteins present in the replication complex. (2) Methods: In this work, highly specific sigma receptor ligands were investigated for their ability to inhibit both SARS-CoV-2 genome replication and virus induced cellular toxicity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 40 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Interactions predicted by our proposed model between JCV major capsid protein VP1 and receptors in brain cells showed a strong enrichment of different neurotransmitters, including serotonin receptors, which is in line with the current literature. For the SARS-Cov-2 spike protein, our model interestingly predicted for all virus variants an interaction with the sigma intracellular receptor 2, which might explain the cytopathic effects of sigma receptor binding ligands reported in the literature (Abate et al 2020, Gordon et al 2020, Ostrov et al 2021). In both cases recent techniques coming from the field of Explainable AI (XAI) allowed us to interpret model predictions and identify those parts of protein sequences, which according to our model mostly influence the prediction of respective protein-protein interactions.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Interactions predicted by our proposed model between JCV major capsid protein VP1 and receptors in brain cells showed a strong enrichment of different neurotransmitters, including serotonin receptors, which is in line with the current literature. For the SARS-Cov-2 spike protein, our model interestingly predicted for all virus variants an interaction with the sigma intracellular receptor 2, which might explain the cytopathic effects of sigma receptor binding ligands reported in the literature (Abate et al 2020, Gordon et al 2020, Ostrov et al 2021). In both cases recent techniques coming from the field of Explainable AI (XAI) allowed us to interpret model predictions and identify those parts of protein sequences, which according to our model mostly influence the prediction of respective protein-protein interactions.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, sigma receptors have been proposed to be involved in the neuronal transmission of SARS-CoV-2 (Yesilkaya et al 2020). They have been suggested as a target for therapeutic intervention (Abate et al 2020, Gordon et al 2020, Ostrov et al 2021). Our results suggest that the observed antiviral effect observed in cell lines treated with sigma receptor binding ligands might be due to a modulated binding of the spike protein, hence inhibiting virus entry into cells.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the SARS-CoV-2 outbreak leading the COVID-19 pandemic, the NP of this field after 2019 reached the highest level, which was verified by cluster 0 in Figures 4B , 5A , 6A . As a multifunctional protein with a broad-spectrum of antimicrobial activities, the molecular docking screening results indicate that LF can be used as a potential drug for the treatment of COVID-19 and also confirmed that a reasonable dose of LF exhibits anti-viral properties in SARS-CoV-2-infected cells ; LF combined with diphenhydramine can reduce the replication of the SARS-CoV-2 by 99% and can also shorten the recovery time of the new crown infection (Mirabelli et al, 2021 ; Ostrov et al, 2021 ). LF inhibits SARS-CoV-2 infection in cell models with multiple modes of action, including blocking viral attachment to cellular heparan sulfate and enhancing interferon responses (Hu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 81%
“… 19 Furthermore, specific agonists of the sigma-1 receptor showed an anti-viral effect but antagonists of this receptor did not. 18 Taken together, these results suggest that the antiviral effect of chloroquine on SARS-CoV-2 relies on several mechanisms but at least in part on agonist binding to sigma receptors, which is responsible for endoplasmic reticulum resistance to virus.…”
Section: Introductionmentioning
confidence: 76%
“… 16 , 17 In addition, coronaviruses, including SARS-CoV-2, activate and utilize endoplasmic reticulum stress and replicate in a modified endoplasmic reticulum-derived compartment. 18 Recent interactomics studies identified that chloroquine interferes with two non-structural viral protein-host protein interactions: nsp6 and the sigma-1 receptor, and Orf9c and the sigma-2 receptor. 14 , 15 Strikingly, both these sigma receptors are known to act as endoplasmic reticulum stress “gatekeepers”.…”
Section: Introductionmentioning
confidence: 99%